MARKETING MIX DECISION FOR PURCHASING BIG MOTOBIKE OF CONSUMERS IN NAKHON PATHOM PROVINCE - Kiyaprat, Miti (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This objectives of this research were to: 1) study the decision behavior to purchase big motorbikes of consumers in Nakhon Pathom Province; 2) study the level of marketing mix in purchasing big motorbikes of consumers in Nakhon Pathom Province; 3) study the level of decision to purchase big motorbikes of consumers in Nakhon Pathom Province; 4) study the marketing mix factors affecting decision to purchase big motorbikes of consumers in Nakhon Pathom Province; and 5) identify guidelines for development of marketing mix in big motorbike business. The sample was 306 consumers in Nakhon Pathom Province who used big motorbikes. The research instrument was a questionnaire constructed by the researcher. Data were analyzed with frequency, percentage, average, standard deviation, correlation analysis, stepwise multiple regression analysis and content analysis. The findings of this research were as follows: 1. Regarding the consumers’ decision behavior to purchase big motorbikes in Nakhon Pathom Province, most of consumers purchased manual transmission big motorbikes of Yamaha brand with 300-650 cc engine displacement because of quality trust. Mostly the consumers purchased big motorbikes from official dealers and the purchased price was not over 300,000 baht. The method of payment was by monthly installment. The main reason for purchasing decision was big motorbike popularity trend in personal travel. 2. Overall the level of marketing mix in purchasing big motorbike was at a medium level. When considering each aspect, the promotion was the highest aspect with a high level, followed by price, product, process, people, place and physical evidence, respectively. 3. Overall the level of decision to purchase big motorbikes was at a high level. When considering each aspect, the post-purchase behavior was the highest aspect with a high level, followed by alternative evaluation, information search and problem recognition, respectively. 4. The marketing mix factors in the aspects of 1) process, 2) physical evidence, 3) place, 4) promotion, 5) price, and 6) people affected decision to purchase big motorbikes of consumers in Nakhon Pathom Province with statistical significance at .05. The marketing mix factors in the aspects of process, physical evidence, place, promotion, price, and people predicted decision to purchase big motorbikes at percentage of 49. 5. The guideline for development of marketing mix factors of big motorbike business to be in accordance with consumers’ needs was that the marketing mix factors affected consumers’ decision to purchase big motorbikes. The dealers should have variety of big motorbikes responding to consumers’ needs, so that they could explore the products and make consideration before purchasing with reasonable price and quality. The process of buying should be with down payment and the interest rate should not exceed the consumers’ payment capacity. The place of distribution should be sufficiently provided. There should be a free gift after sale and an acceptable warranty on a fair period. For consumers’ impression, the personnel should provide sincere services, and the service should be properly and accurately preceded. The service centers or dealer shops should be clean and well partitioned. Article histor : Accepted 18 April 2017 SIMILARITY INDEX = 0.00